2019
DOI: 10.1002/stem.2993
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell-Derived Mesenchymal Stromal Cells Are Functionally and Genetically Different From Bone Marrow-Derived Mesenchymal Stromal Cells

Abstract: There has been considerable interest in the generation of functional mesenchymal stromal cell (MSC) preparations from induced pluripotent stem cells (iPSCs) and this is now regarded as a potential source of unlimited, standardized, high‐quality cells for therapeutic applications in regenerative medicine. Although iMSCs meet minimal criteria for defining MSCs in terms of marker expression, there are substantial differences in terms of trilineage potential, specifically a marked reduction in chondrogenic and adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 87 publications
10
49
1
1
Order By: Relevance
“…It shows that the use of BMSCs and 3D biological scaffold can effectively promote the repair of rat cartilage tissue, and the effect of using both technologies at the same time is signi cantly better than the effect of single use. MSCs have the ability of self-proliferation and multi-directional differentiation, and can replace degenerative cells [15,16], and they can release a variety of biologically active molecules such as TGF-beta, vascular endothelial growth factor, which can work in a paracrine way to inhibit the differentiation of natural killer cells and exerts an anti-in ammatory effect. Studies also showed that scaffold prepared by 3D printing has good physical and chemical properties and cell compatibility, and can induce the differentiation of BMSCs-scaffold complex into cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the use of BMSCs and 3D biological scaffold can effectively promote the repair of rat cartilage tissue, and the effect of using both technologies at the same time is signi cantly better than the effect of single use. MSCs have the ability of self-proliferation and multi-directional differentiation, and can replace degenerative cells [15,16], and they can release a variety of biologically active molecules such as TGF-beta, vascular endothelial growth factor, which can work in a paracrine way to inhibit the differentiation of natural killer cells and exerts an anti-in ammatory effect. Studies also showed that scaffold prepared by 3D printing has good physical and chemical properties and cell compatibility, and can induce the differentiation of BMSCs-scaffold complex into cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…CD90 (Thy-1) appears to play a specific functional role in regulating MSC differentiation 16 but it is not clear that CD73 and CD105 provide a clear biological or mechanistic fingerprint. 17,18 Positive expression of these markers may hide a multitude of problems in terms of cell health and purity and therefore pose questions about the consistency of individual preparations used in preclinical and clinical assessments. Added to this is the common confusion between cell markers and tests of potency which has been unhelpful.…”
Section: Biologymentioning
confidence: 99%
“…While iMSCs meet the minimal criteria for defining MSCs set by the International Society for Cellular Therapy (ISCT) , several reports have indicated that they display altered differentiation propensities, gene expression profiles , and DNA methylation profiles when compared with primary MSCs. To reveal more approximately these differences, researchers from the laboratory of Frank Barry (National University of Ireland, Galway, Ireland) recently conducted a range of phenotypic, functional, and genetic comparisons between iMSCs and BM‐MSCs . In their new Stem Cells article, Xu et al reveal that iMSCs display high levels of KDR and MSX2 and lower levels of PDGFRα gene expression when compared with BM‐MSCs and, therefore, bear a closer resemblance to VPCs, a similar stem cell population that requires different inductive conditions.…”
Section: Featured Articlesmentioning
confidence: 99%
“…The directed differentiation of stem cells such as MSCs from patient‐specific induced pluripotent stem cells (iPSCs) is an exciting alternative, although questions remain regarding the similarity of these cells to their endogenous counterparts when using currently described differentiation protocols. In our first Featured Article from Stem Cells this month, Xu et al report that while iPSCs‐MSCs (or iMSCs) and bone marrow (BM)‐derived MSCs broadly share phenotypic traits in terms of standard markers and gene expression, their analysis uncovered marked differences in the levels of genes associated with vascular progenitor cells (VPCs), suggesting that iMSCs more closely resemble another related cell type . In a Related Article from Stem Cells Translational Medicine , Brick et al describe the production of MSC‐like progenitor cells from iPSCs that can promote neurite sprouting and axon elongation in an embryonic dorsal root ganglion explant culture model and, therefore, may find use as a replacement for MSCs in nerve regeneration and repair .…”
mentioning
confidence: 99%